Present, Past and Future of Nuclear Medicine in Bangladesh (Bangladesh Journal of Nuclear Medicine, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22485 Bangladesh J. Nuclear Med. 17(1): 08-09, January 2014